Clinical Features of Combined Central Retinal Artery and Vein Occlusion - Hao Wang; Yongye Chang; Fen Zhang; Rong Yang; Suxia Yan; Jieying Dong; Minglian Zhang; Shaomin Peng (Journal of Ophthalmology)
Purpose. To describe the clinical features of combined central retinal artery and vein occlusion (CCRAVO). Methods. This retrospective study included 33 admitted patients (33 eyes) who had CCRAVO. Clinical data, such as age, gender, best-corrected visual acuity (BCVA), intraocular pressure (IOP), findings on fundus color photography and fundus fluorescein angiography (FFA), and information about follow-up, were collected and analyzed. Results. The age of the patients with CCRAVO ranged from 22 to 78 years, with a mean of 48.8 ± 14.1 years. At presentation, BCVA of the involved eyes ranged from no light perception (NLP) to 20/20. In addition, 45.5% (15/33) of the eyes had BCVA of finger counting (FC) or below, whereas 12.1% (4/33) had BCVA of 20/60 or above. The IOP was lower in the involved eyes than in the fellow eyes (15.0 ± 3.0 mmHg vs. 16.4 ± 2.3 mmHg, p=0.03). Ophthalmoscopic examination showed changes in both central retinal artery occlusion (CRAO) and central retinal vein occlusion (CRVO), including retinal hemorrhage, retinal ischemic whitening, optic disc hyperemia and/or edema, venous dilation and tortuosity, cotton wool spot (CWS), and Roth’s spot. FFA showed prolonged arm-to-retina time (ART) and retinal arteriovenous passage time (RAP) (17.1 ± 4.9 s and 12.1 ± 8.8 s, respectively). Capillary nonperfusion (CNP) was seen in 21 eyes (63.6%), and in 14 (42.2%) of these, CNP was larger than 10 disc areas. At 2 to 3 weeks after presentation, BCVA improved in 23 eyes (71.9%) and further deteriorated in 5 eyes (15.6%). Retinal ischemic whitening improved in more than half of the eyes, whereas retinal hemorrhage increased in nearly half of the eyes. Follow-up ranged from 6 to 56 months. Seven patients were lost to follow-up. At final follow-up, six eyes had a visual acuity of 20/60 or greater, but 6 eyes had FC or worse. Four eyes developed neovascularization on follow-up. Conclusion. CCRAVO is a sight-threatening entity. Manifestations of CRAO and CRVO can be seen simultaneously in the early stage of disease, and CRVO may play a more important role in the development of CCRAVO.